UN NOU MODEL DE DIAGNOSTICARE A TULBURĂRILOR SPECIFICE DE PERSONALITATE - USM ADMIN (Moldova State University, 2010)
The author presented in this article the definition for specific personality disorders, as well as the basic concepts for a new model in personality disorders diagnosis. She emphasizes the importance of introduction of new elaborated factors personality disorders diagnosis. Those factors (obligation of a symptom, weight of a symptom and the intensity coefficient), which were implemented and tested in her dissertation, provided the elaborated system with desired sharpness.